1976
DOI: 10.1002/jcp.1040880102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged quiescence on nuclei and chromatin of WI‐38 fibroblasts

Abstract: DNA synthesis and cell division are markedly reduced in confluent mono-layers of WI-38 diploid fibroblasts, but resume again if the depleted medium is replaced by fresh medium containing 10% fetal calf serum. If the cells are kept quiescent for prolonged periods of time after confluence (1 or 2 weeks), the fraction of cells that can be stimulated to proliferate by fresh serum decreases and the length of the prereplicative phase increases. The template activity of isolated nuclei decreases with increasing time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 51 publications
3
20
0
1
Order By: Relevance
“…The enhancement of growth inhibitory activity in our assay by a deep Go state of quiescence appears to parallel the results obtained in heterokaryon experiments (1,6,26,30,39), suggesting that growth inhibition may be mediated by similar mechanisms in both assays. On the other hand, it has been reported that HeLa cells exhibit a dominant phenotype in heterokaryon fusions, i.e., induce DNA replication in nuclei from quiescent or senescent cells (19,23,26,39).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The enhancement of growth inhibitory activity in our assay by a deep Go state of quiescence appears to parallel the results obtained in heterokaryon experiments (1,6,26,30,39), suggesting that growth inhibition may be mediated by similar mechanisms in both assays. On the other hand, it has been reported that HeLa cells exhibit a dominant phenotype in heterokaryon fusions, i.e., induce DNA replication in nuclei from quiescent or senescent cells (19,23,26,39).…”
Section: Discussionsupporting
confidence: 84%
“…Genomic DNAs were prepared from quiescent cultures of W138 human embryo fibroblasts in which quiescence had been induced either by density arrest in medium containing 10% fetal calf serum or by serum deprivation in medium containing 0.5% fetal calf serum. The latter (low-serum) condition has previously been shown to induce a characteristic deep Go state of quiescence that mediates growth inhibition in heterokaryon experiments (1,6,26,30,39). These DNAs were mixed with the marker plasmid pRSVneo (10) and transfected into HeLa S3 cells growing in monolayer culture.…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with the idea that cellular ageing is associated with events occurring after the loss of the cells' ability to divide Evans, 1976b). In sup port of this suggestion, it has been reported that changes occurring in RNA transcription and in the kinetic properties of cells held 'quiescent' for long periods were similar to those occurring during the later part of the in vitro life span (Augenlicht and Baserga, 1974;Evans, 1976b;Rossini et al, 1976). Our own preliminary studies with early passage ( p i3/25) He 125 cells held in 'quiescence' for 11 days by repeated medium changing also confirm this observation since a decrease in template activity was noted in these cells compared with repli cate cultures which had just attained 'quies cence' (370 compared with 580cpm/jug DNA).…”
Section: Discussionsupporting
confidence: 79%
“…Resting lymphocytes may be in a deeper Go state and may, upon stimulation i, amino-acid-deficient medium, be partially activated to become arrested in a state equivalent to that of quiescent densitydependent cells. The existence of various depths of GO state has been recently suggested [24].…”
Section: Discussionmentioning
confidence: 99%